2015
DOI: 10.3390/nano5020425
|View full text |Cite
|
Sign up to set email alerts
|

Meso-Structuring of SiCN Ceramics by Polystyrene Templates

Abstract: A simple one-pot synthesis of well-defined PS-silazane nano-composites (polystyrene, PS) is described. In contrast to the, thus far, used two-step procedure ((1) assembly of a PS template bed and (2) careful filling of the voids between the PS spheres), which is restricted to macro structuring, we are able to simply mix the PS template and a commercially available silazane precursor HTT-1800 in toluene. The key is the alteration of the zeta potential of the PS template leading to a homogeneous dispersion in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
(48 reference statements)
0
10
0
Order By: Relevance
“…8 So far, numerous porous silicon-based ceramics were developed by the PDC route. Using these preceramic polymers, most of the nanoporous PDCs were prepared by a template-assisted technique including hard templates [9][10][11][12][13] and soft templates (block copolymers), [14][15][16] exclusively. Generally, in PDCs, the pores are generated by the evolution of small molecules like CH 4 and H 2 during the pyrolytic conversion process.…”
Section: Introductionmentioning
confidence: 99%
“…8 So far, numerous porous silicon-based ceramics were developed by the PDC route. Using these preceramic polymers, most of the nanoporous PDCs were prepared by a template-assisted technique including hard templates [9][10][11][12][13] and soft templates (block copolymers), [14][15][16] exclusively. Generally, in PDCs, the pores are generated by the evolution of small molecules like CH 4 and H 2 during the pyrolytic conversion process.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ewert et al . showed that polystyrene could be used as a soft template to generate a defined mesostructure in SiCN materials.…”
Section: Figurementioning
confidence: 99%
“…[13,14] The silicon carbonitride (SiCN) support is thermally very robust, chemically inert, and attractive for generating rather smallm etal nanoparticles in such supports. [15] In addition, we introduced strategies to mesostructure SiCN [16][17][18] and becamei nterested in combining both approaches to synthesize highlya ctive and selective base-metal catalysts. [19] Herein, we report novel mesostructured Ni@SiCN nanocomposite materials easy to synthesize ands cale up.…”
mentioning
confidence: 99%
See 2 more Smart Citations